K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 7 2021

\(a,A=\left(1-\frac{\sqrt{x}}{\sqrt{x}+1}\right):\left(\frac{\sqrt{x}+3}{\sqrt{x}-2}-\frac{\sqrt{x}+2}{\sqrt{x}-3}+\frac{\sqrt{x}+2}{x-5\sqrt{x}+6}\right)\)

\(A=\frac{\sqrt{x}+1-\sqrt{x}}{\sqrt{x}+1}:\frac{x-9-x+4+\sqrt{x}+2}{x-5\sqrt{x}+6}\)

\(A=\frac{1}{\sqrt{x}+1}:\frac{\sqrt{x}-3}{\left(\sqrt{x}-3\right)\left(\sqrt{x}-2\right)}\)

\(A=\frac{\sqrt{x}-2}{\sqrt{x}+1}=\frac{\sqrt{x}+1-3}{\sqrt{x}+1}=1-\frac{3}{\sqrt{x}+1}\)

\(< =>b,3⋮\sqrt{x}+1\)

lập bảng thì ra đc

\(x=4;0\)

21 tháng 7 2021

??? ở đâu

=(căn 3-1)^2

12 tháng 7 2021

undefined

Ta có: \(\dfrac{1}{2+\sqrt{3}}+\sqrt{3}\)

\(=2-\sqrt{3}+\sqrt{3}\)

=2

23 tháng 10 2023

\(\dfrac{6}{\sqrt{2}-\sqrt{3}+3}\)

\(=\dfrac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{\left(\sqrt{2}-\sqrt{3}\right)^2-9}\)

\(=\dfrac{6\left(\sqrt{2}-\sqrt{3}-3\right)}{-4-2\sqrt{6}}\)

\(=\dfrac{-3\left(\sqrt{2}-\sqrt{3}-3\right)}{2+\sqrt{6}}=\dfrac{-3\left(\sqrt{6}-2\right)\left(\sqrt{2}-\sqrt{3}-3\right)}{2}\)

 

Ta có: \(\dfrac{\sqrt{8-2\sqrt{12}}}{\sqrt{3}-1}\)

\(=\dfrac{\sqrt{\left(\sqrt{6}-\sqrt{2}\right)^2}}{\sqrt{3}-1}\)

\(=\sqrt{2}\)

Ta có: \(\dfrac{2\sqrt{3}}{\sqrt{3}+\sqrt{2}}+\sqrt{24}\)

\(=2\sqrt{3}\left(\sqrt{3}-\sqrt{2}\right)+2\sqrt{6}\)

\(=6-2\sqrt{6}+2\sqrt{6}\)

=6

11 tháng 7 2017

\(\frac{3x+9\sqrt{x}}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}=\frac{3\sqrt{x}\left(\sqrt{x}+3\right)}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-3\right)}=\frac{3\sqrt{x}}{\sqrt{x}-3}\)